Software Testing Automation of VR-Based Systems With Haptic Interfaces. (11th June 2020) - Corrêa, Cléber G; Delamaro, Márcio E; Chaim, Marcos L; Nunes, Fátima L S
Abstract: As software systems have increased in complexity, manual testing has become harder or even infeasible. In addition, each test phase and application domain may have its idiosyncrasies in relation to testing automation. Techniques and tools to automate test oracles in domains such as graphical user interfaces are available; nevertheless, they are scarce in the virtual reality (VR) realm. We present an approach to automate software testing in VR-based systems with haptic interfaces—interfaces that allow bidirectional communication during human–computer interaction, capturing movements and providing touch feedback. It deals with the complexity and characteristics of haptic interfaces to apply the record and playback technique. Our approach also provides inference rules to identify possible faulty modules of the system under testing. A case study was performed with three systems: a system with primitive virtual objects, a dental anesthesia simulator and a game. Faulty versions of the systems were created by seeding faults manually and by using mutation operators. The results showed that 100% of the manually seeded faults and 93% of mutants were detected. Moreover, the inference rules helped identify the faulty modules of the systems, suggesting that the approach improves the test activity in VR-based systems with haptic interfaces.